Islamic Bank Customer Satisfaction and Services During the COVID-19 Pandemic - Riduwan, Riduwan; Setyono, Hendro; Yuliana, Monikka; Jannah, Siti Salma Miftahul (Universitas Muhammadiyah Yogyakarta, 2022)
The COVID-19 pandemic has negatively impacted the Islamic banking industry by increasing non-performing financing, decreasing savings, and weakening annual performance. This condition, if not anticipated, can lead to bankruptcy. Therefore, customers need to get the best service so that their loyalty is maintained even though the conditions of Islamic banks are difficult. This study analyses customer satisfaction toward Islamic banks services during the COVID-19 pandemic. The respondents are 308 customers. The sampling method uses purposive sampling, and the data processing uses the Customer Satisfaction Index (CSI) model. The results of this study indicate that customers are satisfied with Islamic banks' services. So, they are willing to recommend other parties to become bank customers, not transfer funds to other Islamic banks, will not move to conventional banks, and not withdraw deposits. However, this study has limitations because it has not included social performance as a factor that affects loyalty. In addition, most respondents are Muslim, so future research is recommended to analyze satisfaction by including these two factors. Furthermore, these findings provide value for policy implications and recommendations for Islamic banks and stakeholders to increase satisfaction and service.